Efeito in vitro do açaí sobre a cor, dureza e rugosidade de uma resina composta nanoparticulada - Garcia, Larissa de Oliveira (2021)
The staining of composite resin restorations by eating food dyes worries dentists and patients. Objectives: To evaluate the in vitro effect of acai berry exposure on the color, hardness, and surface roughness of composite resins. Materials and methods: 75 discs (2 mm height, 8 mm diameter) of Filtek composite resin™ Z350 (color A1) were divided into 3 experimental groups (n=25) according to the treatments with artificial saliva, acai sorbet, and acai pulp juice. The discs were immersed in 6 mL of the solution for 15 min, 3×/day (interval of 30 min) for 14 days and, kept in the oven at 37ºC the rest of the time, immersed in artificial saliva. Knoop hardness (primary outcome), roughness and color (CIELAB) were analyzed before and after treatment. The pH ranged from 6.76 to 7.0 for saliva, 3.85-3.89 for sorbet and 4.95-5.01 for juice. Result: None of the three variables presented normal distribution (Shapiro Wilk test; p<0.05). The ANOVA on Ranks showed no statistical difference between the ΔR (p=0.998) and ΔD (p=0.737) groups. There was a statistically significant difference between the artificial saliva and juice groups (p=0.019) for ΔE (Dunn’s test). For all groups ΔE was lower than 3.3. Conclusion: The acai berry did not alter the surface properties of the composite resin (hardness and roughness), but there was a clinically acceptable staining for all treatments.